Comparação do efeito do método de medição com contato e sem contato na rugosidade - Motta Neto, Walter dos Santos (2017)
The aim of this work is to compare the effect of contact and non-contact measurement methods of roughness on the values of roughness parameters Ra, Rq, Rv, Rz, Rt, Rp, Rsk and Rku in samples made of commercial aluminum, SAE 1020 carbon steel and gray cast iron, obtained by turning and milling processes. A complete factorial 3x2x2x2 design of experiments was proposed for the fabrication of the samples, in which four factors (sample material, machining process, feed rate and depth of cut) were considered. The roughness parameters were obtained by measuring the samples by means of an electromechanical rugosimeter with diamond tips of radius equal to 2 μm and 5 μm. For comparative purposes, the samples were measured by white light interferometry, and the results found were adopted as reference for determination of the difference between the values of the roughness parameters obtained by the two methods. The uncertainty associated with the measurement of all evaluated parameters was estimated by applying the GUM and Monte Carlo methods. According to the results obtained, the values of the roughness parameters Ra, Rq, Rv, Rz, Rt, Rp, Rsk and Rku were influenced by the material, the machining process, the cutting conditions and the type of measurement used. The percentage differences observed between the contact and non-contact measurements in aluminum milling were 55% for Ra and Rq, while for Rp, Rv, Rz and Rt this difference was close to 75%. In milling gray cast iron the percentage difference values were equal to 70% for Ra and Rq, and 80% for the parameters Rp, Rv, Rz and Rt.